Geo-environmental monitoring territory of Kazakhstan for sustainable development (Experimental biology, 2015)
The state network of observation points is only 20% of the optimal quantity of the equipment of measuring equipment from 40 to 80% of the required level. The lack of interdepartmental coordination of the monitoring systems of different ministries and agencies does not allow to carry out to the full the objective assessment of the geological development, state of the environment and to obtain timely operational information.
Keywords: geoecology; monitoring; sustainable development; Kazakhstan; space technology